Invisible Stories: A Phenomenological Study of Bi and Trans Parent Experiences Within Elementary Schools in the Southwestern United States. Issue 12 (15th October 2022) - Kappus, Becky D.; Lucero, Leanna; Cascalheira, Cory J.; Ijebor, Ellen E.
ABSTRACT: Heteronormativity, family hegemony, and gender biases in K-12 education threaten child safety, parental dignity, and identity among queer families. While prior research examined the experiences of queer parents—specifically those of lesbian and gay parents—empirical attention to school-related experiences of trans and bi parents is lacking. Hence, this phenomenological study focuses on the PK-12 school-related experiences of bi and trans parents. Using queer theory as a theoretical framework, we review relevant literature on family hegemony, gender biases, and heteronormativity within school settings and its impact on children with queer families. Then, we discuss the methods and analysis used to understand the experiences of bi and trans parent participants. Analysis revealed four themes: (a) concern for the child ; (b) value for diversity ; (c) heteronormative nature of schools ; and (d) importance of inclusivity . Finally, we provide recommendations on ways school personnel can better support trans and bi parents and their children.